Development of Interactive IPAS Teaching Materials Using Wordwall Applications Based on Problem Based Learning (PBL) Models in Fourth Grade Elementary Schools - Ellsy Rahmadani Putri; Desyandri; Leni Zahara; Rayendra (Postgraduate, University of Mataram, 2025)
This research is motivated by the fact that teachers are not yet fully utilizing the available IT in schools. There is a lack of development of innovative, interactive, and enjoyable teaching materials for students. Therefore, teachers need to improve their ability to process technology-based teaching materials to encourage student enthusiasm for learning. Furthermore, the PBL model has never been used in learning. Based on these problems, this study aims to develop interactive IPAS teaching materials using a wordwall application based on the Problem Based Learning (PBL) model in grade IV elementary schools that are valid, practical, and effective. This type of research is research and development (R&D) using the ADDIE model. The ADDIE model consists of five steps: analysis, design, development, implementation, and evaluation. The designed teaching materials were then validated by a validator using a validation sheet in the form of a questionnaire. Product validation consisted of material experts, media experts, and language experts. For product practicality, it was carried out by filling out questionnaires of teacher responses and student responses. Then, for effectiveness, it was carried out by giving evaluation questions to students. The trial subjects were at SDN 01 Patamuan and the research subjects were at SDN 03 Patamuan and SDN 05 Patamuan. The results of the study obtained a validity level of 95% from the material aspect in the very valid category, 92.5% from the media aspect in the very valid category and 95% from the language aspect in the very valid category. Based on the results of teacher responses and student responses in the trial school, it is known that learning using interactive teaching materials is very practical with a percentage of practicality from teacher responses in the trial school of 92.5%, and from student responses of 93.9%. The percentage of teacher responses in the research school is 95% and the percentage of student responses is 96%. The effectiveness results show very effective results with a percentage increase in student learning outcomes from 74.5% to 97.3% with a N-gain test value of 0.925 or 92.5% in the effective category. Thus, it can be concluded that interactive science teaching materials using wordwall applications based on the Problem Based Learning (PBL) model in grade IV of elementary school are valid, practical and effective. to be used in the learning process.